2018
DOI: 10.2147/ott.s185997
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinol inhibits the growth, migration and invasion of hepatocellular carcinoma cells via regulating the PI3K-AKT signaling pathway

Abstract: BackgroundTanshinol is an active constituent of Salvia miltiorrhiza and possess anti-inflammatory, antioxidant, and anti-bacterial activity. Herein, we explored the role of tanshinol on the growth and aggressiveness of hepatocellular carcinoma (HCC) cells in vitro and in vivo.Materials and methodsThe proliferation of a panel of HCC cell lines was measured using MTT assay. The expressions of phosphatidylinositol 3 kinase (PI3K) and protein kinase B (AKT) were detected by immunofluorescence staining and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Taken together, these results demonstrated that MAFG-AS1 may promote HCC progression through inhibition of miR-6852. The effect of MAFG-AS1 on expression of members of the STAT3, Wnt/β-catenin and PI3K/AKT signaling pathways were determined, which are related to proliferation, migration and invasion of HCC (19). Western blotting showed that MAFG-AS1 silencing only suppressed the activation of the PI3K/AKT signaling pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these results demonstrated that MAFG-AS1 may promote HCC progression through inhibition of miR-6852. The effect of MAFG-AS1 on expression of members of the STAT3, Wnt/β-catenin and PI3K/AKT signaling pathways were determined, which are related to proliferation, migration and invasion of HCC (19). Western blotting showed that MAFG-AS1 silencing only suppressed the activation of the PI3K/AKT signaling pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the PI3K-Akt signaling pathway, numerous studies have also reported its crucial role in the process of HCC. The PI3K-Akt signaling pathway has been widely reported to act as a key factor related to cell proliferation, invasion, metastasis, and apoptosis as well as the cell cycle [52][53][54][55][56]. Given that, we speculated that the molecular mechanism of CELSR3 in promoting cell proliferation, invasion, and migration, as well as inhibiting apoptosis may be closely associated with the cell cycle, DNA replication, and the PI3K-Akt signaling pathway through interacting with its co-expressed genes.…”
Section: Discussionmentioning
confidence: 93%
“…no. IT4738; G-Biosciences) in the culture media according to the manufacturer's instructions and as described previously (31,32).…”
Section: Methodsmentioning
confidence: 99%